Facile One‐Pot, One‐Step Synthesis of a Carbon Nanoarchitecture for an Advanced Multifunctonal Electrocatalyst1. (5th May 2014) - Wen, Zhenhai; Ci, Suqin; Hou, Yang; Chen, Junhong
Abstract A one‐pot/one‐step synthesis strategy was developed for the preparation of a nitrogen‐doped carbon nanoarchitecture with graphene‐nanosheet growth on the inner surface of carbon nanotubes (CNTs). The N‐graphene/CNT hybrids exhibit outstanding electrocatalytic activity for several important electrochemical reactions as a result of their unique morphology and defect structures, such as high but uniform nitrogen doping, graphene insertion into CNTs, considerable surface area, and the presence of iron nanoparticles. The high‐yield synthetic process features high efficiency, low‐cost, straightforward operation, and simple equipment.